Peningkatan kesadaran warga sekitar sungai luk, desa Sambik Bangkol terhadap mitigasi banjir lokal melalui sosialisasi penerapan sistem eko-hidrolik dan “resik-resik kali” - Muhammad Khalis Ilmi; Hidayat, Ari Ramadhan; Swahip; Hidayati, Nurul; Semengasbumi, Ringgi Puteri; Wahyuningsih, Titik; Efendy, Anwar; Hamdani, Hafiz; Toyyib, Mukhtar; Pratama, Dika (Rengganis Jurnal Pengabdian Masyarakat, 2025)
In 2013 and 2020, local flooding events occurred along the river segment adjacent to the area of Luk Barat Hamlet. These incidents resulted in the collapse of a resident’s wall, damage to structural elements of the Luk River Bridge, the blockage of a nearby spring, and the inundation of several houses within Luk Barat Hamlet. It is anticipated that similar disaster events may recur in the future. Therefore, it is necessary to enhance community education regarding flood mitigation through the dissemination of the Eco-Hydraulic System and the “Resik-Resik Kali”. The method employed in this community engagement activity involved a knowledge transfer approach through socialization sessions, followed by participatory discussions with local residents. The program concluded with the distribution of banana seedlings and the implementation of a “resik-resik kali” activity. This community engagement initiative successfully increased residents’ understanding of potential flood hazards and their associated risks, the benefits of applying an eco-hydraulic system utilizing banana trees for local flood mitigation, as well as practical insights into the “resik-resik kali” activities that have been widely implemented in other regions.